Pelatihan Teknologi Bio-induksi untuk Petani Gaharu di Desa Pejaring, Kabupaten Lombok Timur - I Gde Adi Suryawan Wangiyana; Sad Kurniati Wanitaningsih; Lutfi Anggadhania (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Agar wood farmer of Pejaring Village have used traditional method to induce resin formation on agarwood tree. They used mechanical method induction by nail and machete tools as well as chemical method induction by chemical liquid that the called by “infus”. These traditional methods influenced resin formation on agarwood tree at their agarwood plantation. That resin production was low in productivity and low in efficiency. The purpose of this community service was to conducted workshop of bio-induction technology for Pejaring Village agarwood farmer to solve their problem. Agarwood farmer of Pejaring Village were directly involved in all bio-induction training activity. This training was started by socialization of program through FGD with Agarwood Farmer of Pejaring Villange. Practical stage was started by selecting agarwood tree for sample by themselves. After selecting process has been done, training continued by bio-induction of agarwood sample using bore and injecting method also by themselves. The last stage was monitoring and evaluating of resin production on agarwood sample as result of bio-induction. In this stage, they got opportunity to give self-assessment of those resin production by organoleptic test. Bio-induction technology could stimulate resin formation on agarwood tree sample at 3 months after induction. This result was much better comparing to the result of traditional induction method that they used to conducted. Organoleptic test has confirmed that resin has quite good fragrance quality. It could be concluded that Pejaring Village agarwood farmers have understood about bio-induction technique and could applied that technology to replace traditional technology.